GOROAWASE DALAM BAHASA JEPANG - , Ningrum Tresnasari ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The research discussed about goroawase, i.e.: a language game in Japanese which is later used as a technique to memorize important numbers. The aim of the research is to describe the forming pattern of the principles in reading goroawase